Respostas

2013-11-26T17:09:17-02:00
A=(aij) 3x4 sabendo que aij = 2i-3j.

aij
a11 = 2 * 1 -3 *  1= 2 - (-3) = a11 = 5
a12 = 
2 * 1-3 *  2= 2 - (-6) = a12 = 8
a13 = 
2 * 1-3 *  3= 2 - (-9) = a13 = 11
a14 = 
2 * 1-3 *  4= 2 - (-12) = a14 = 14
a21 = 
2 * 2-3 *  1= 4 - (-3) = a21 = 7
a22 = 
2 * 2-3 *  2= 4 - (-6) = a22 = 10
a23 = 
2 * 2-3 *  3= 4 - (-9) = a23 = 13
a24 = 
2 * 2-3 *  4= 4 - (-12) = a24 = 16
a31 = 
2 * 3-3 *  1= 6 - (-3) = a31 = 9
a32 = 
2 * 3-3 *  2= 6 - (-6) = a32 = 12
a33 = 
2 * 3-3 *  3= 6 - (-9) = a33 = 15
a34 =  
2 * 3-3 * 4= 6 - (-12) = a34 = 18

Sua matriz fica assim...

5   8   11   14   
7   10  13  16
9   12  15  18
3 5 3